Comparison of Choledochoduodenostomy and Hepaticogastrostomy for EUS-Guided Biliary Drainage: A Meta-Analysis - Li, Jiasu; Tang, Jian; Liu, Feng; Fang, Jun (Frontiers in Surgery, 2022)
Background: Although endoscopic ultrasound-guided choledochoduodenostomy (EUS-CDS) or hepaticogastrostomy (EUS-HGS) has emerged as an option for patients of failed endoscopic retrograde cholangiopancreatography (ERCP), there has no agreement on which approach is preferred. Therefore, a meta-analysis was performed to examine the two methods. Methods: We performed a comprehensive search in databases of PubMed, Embase and Cochrane library to find relevant studies reporting the efficacy and safety of the two EUS-guided biliary drainage methods. Results: 12 studies with 623 patients (EUS-CDS: 303, EUS-HGS: 320) were included. The cumulative technical success and clinical success for EUS-CDS and EUS-HGS was 95.0% (288/303), 93.1% (268/288), and 96.6% (309/320), 91.3% (282/309), respectively. Compared with EUS-HGS, the pooled odds ratio (OR) was 0.74 [95% confidence interval (CI) 0.33-1.65; p=0.46] for EUS-CDS technical success and 0.94 (95% CI 0.56-1.59; p=0.83) for clinical success. The pooled difference in means of procedure time of EUS-CDS and EUS-HGS was -2.68 (95% CI -5.12 to -0.24; p=0.03). The cumulative early adverse events for EUS-CDS and EUS-HGS was 12.2% (37/303) and 17.5% (56/320), respectively. Compared with EUS-HGS, the pooled OR of early adverse events for EUS-CDS was 0.58 (95% CI: 0.36-0.93; p=0.02). Conclusion: The available literature suggests EUS-CDS and EUS-HGS have equal high technical and clinical success, while EUS-CDS with a slightly short procedure time and with little early adverse events compared to EUS-HGS.